The Role of Village Apparatus in Village Fund Management Accountability (Study in Sumberdadi Village, Trenggalek District): The Role of Village Apparatus in Village Fund Management Accountability (Study in Sumberdadi Village, Trenggalek District) - Meme Rukmini; Bothy Dewandaru; Octaviana Wahyu Prihardini; Mayciella So (Universitas Islam Lamongan, 2023)
The biggest report in the media discusses a lot of corruption cases that ensnare village heads, so it is necessary to prepare clear mechanisms and regulations regarding this matter. Regulation of the Minister of Home Affairs No. 113 of 2014 concerning guidelines for village financial management is expected to be a guideline in village fund management because it covers various village financial management procedures ranging from planning, implementation, administration, reporting to accountability. This study aims to examine the role of village officials in carrying out accountability for village fund management. The population and research sample of all village officials in Sumberdadi Trenggalek Village amounted to 28 people. The data analysis method used in this study is to use a descriptive method with a quantitative approach, which is a method that describes the actual situation systematically, factually and accurately regarding the role of village officials in accountability for village fund management. The results of this study play the role of the Sumberdadi Trenggalek Village village apparatus in the accountability of village fund management plays a very important role.